BIOECOLOGY OF GIANT FRESHWATER PRAWNS (MACROBRACHIUM ROSENBERGII) IN THE BILAH RIVER, LABUHANBATU DISTRICT, NORTH SUMATERA - Siti Aminah Nasution; Rivo Hasper Dimenta (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2022)
Giant freshwater prawns (Macrobrachium rossenbergii) were still been the favorite prawn catch of local fishermen in the Labuhanbatu district. This raises concerns for the survival of these animals. Therefore, it is necessary to conduct a study to obtain bioecological information on this giant freshwater, giant prawns in the Bilah river especially inform about condition the abundance based on gonad maturity levels, and the growth patterns of Giant freshwater prawns (M. rossenbergii). This study was conducted at 3 stations around the Bilah river. These stations were determined using a purposive sampling method. Furthermore, sampling was carried out using fishing nets. After that, the caught fish were analyzed to find out the Fulton’s condition factor, the abundance of prawns based on gonad maturity levels, and the growth patterns. The results of growth patterns analysis which calculate from the relationship of carapace length and body weight of M. rossenbergii caught were showed negative allometric category (b value 1.88 to 2.577). Meanwhile, the abundance of giant freshwater prawns based on gonad maturity levels for males and females were dominated by immature prawns (ranging from 46.15 to 54.65%).